Desintegración familiar y desempeño emocional en el aula en estudiantes del cuarto ciclo de primaria en la Institución Educativa Miguel Acosta Oyarce, Caballococha 2025 - Vera Delgado de Jorge, Maria Sadit (2026)
The study aimed to analyze the relationship between family disintegration and emotional performance in the classroom among fourth-cycle primary students at Miguel Acosta Oyarce Educational Institution (Caballococha, 2025). A quantitative, relational approach was adopted, employing a bivariate, field-based, and cross sectional design. The study population and sample consisted of 141 students. Data were collected using a questionnaire and an observation guide, both validated through expert judgment. Statistical analyses revealed that while the variable family disintegration followed a normal distribution (p = .200), the remaining variables did not; therefore, Spearman’s nonparametric correlation was applied. Results indicated a moderate negative relationship between family disintegration and emotional performance (rho = -0.449, p < .001), as well as a low negative relationship between the economic dimension of family disintegration and emotional performance (rho = -0.278, p = .001). In conclusion, lower levels of family disintegration were associated with higher emotional performance in the school context, underscoring the crucial role of the family environment in children’s socio-emotional development.